2019
DOI: 10.3390/ijerph16091578
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Impact of and Adaptation to Extreme Heat and Cold of Farmers in the Food Bowl of Nepal

Abstract: Farmers worldwide have to deal with increasing climate variability and weather extremes. Most of the previous research has focused on impacts on agricultural production, but little is known about the related social and economic impacts on farmers. In this study, we investigated the social and economic impact of extreme weather events (EWE) on farmers in Nepal, and explored how they coped with and adapted to heat waves and cold spells between 2012 and 2017. To address these aims, we conducted a survey of 350 fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 105 publications
(189 reference statements)
1
26
0
1
Order By: Relevance
“…Other commonly used preventive measures include acclimatization ( 52 , 116 ), HRI training ( 63 , 116 , 117 ), wearing sunglasses and sunscreen ( 55 , 63 ), and the use of rest stations or fans ( 56 , 116 ). Preventative measures that were less common among the reviewed studies included eating a traditional diet ( 119 ) and bathing in cold water ( 53 , 116 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other commonly used preventive measures include acclimatization ( 52 , 116 ), HRI training ( 63 , 116 , 117 ), wearing sunglasses and sunscreen ( 55 , 63 ), and the use of rest stations or fans ( 56 , 116 ). Preventative measures that were less common among the reviewed studies included eating a traditional diet ( 119 ) and bathing in cold water ( 53 , 116 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies that have tried to quantify the heat effect on workers' productivity and to estimate the economic impact are still very few (Roson and Van der Mensbrugghe, 2012;Chinnadurai et al, 2016;Kjellstrom, 2016;Takakura et al, 2017;Budhathoki and Zander, 2019;Vanos et al, 2019). However, the exposure to heat stress is expected to increase significantly in the next years because of climate change (Mora et al, 2017) also in areas where the worker population is not used to fighting this phenomenon (Kjellstrom et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study (Day et al, 2019), the authors reported that the heat-related PL is one of the most prominent "market impact" in studies on the economic effects of climate change. However, field studies that have tried to quantify the economic impact of heat stress based on worker's productivity are still very uncommon (Budhathoki and Zander, 2019;Vanos et al, 2019), and there is no agreement among economists on which methods for estimations of these heat impacts would ensure reliability and validity for future projections (Kjellstrom et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Em estudos italiano (Cecchini, Bedini, Mosetti, Marino, & Stasi, 2018), coreano (Park, Park, Kim, & Choi, 2020) e nepalĂȘs (Budhathoki & Zander, 2019) verificaram-se como evidĂȘncias de percepção de riscos ocupacionais fĂ­sicos em agricultores rurais de soja e arroz, eventos como frio, calor, umidade, ruĂ­do, radiaçÔes nĂŁo ionizantes e vibraçÔes. SĂŁo achados semelhantes ao deste estudo, Ă  medida que identifica e atua na prevenção de danos fĂ­sicos no trabalho, a fim de evitar doenças ocupacionais, relacionadas principalmente: Ă  sĂ­ndrome de vibração mĂŁo-braço em agricultores que trabalharam ou tĂȘm histĂłrico laboral em locais com ferramentas vibratĂłrias, como motosserras; distĂșrbios cutĂąneos por radiação solar, como cĂąncer de pele, doença ocular (catarata) e insolação, devido ao trabalho em local quente; perda auditiva induzida por ruĂ­do, como som de tratores e mĂĄquinas agrĂ­colas em ambientes laborais com ruĂ­do contĂ­nuo maior de 85 decibĂ©is por mais de trĂȘs anos; estresse por calor, Research, Society and Development, v. 9, n. 11, e739119543, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.9543 como dores de cabeça, fadiga e desmaios; estresse por frio e umidade, como o aumento na ocorrĂȘncia de gripe viral, tosse, diarreia, asma e pneumonia.…”
Section: Discussionunclassified